Impact Analysis of Structural and Non-Structural Program and Collaboration of Stakeholder to Productivity of Sustainable Flood Mitigation Management - Owin Jamasy, Djamaludin; Siagian, Edison; Movianto, Gunawan Eko; Pranoto, Yuni; Khairun Nisa, Mohd Arshad (2023)
The flood occurred in 3 Cis in Banten Province dan 5 rivers in Ambon-Seram Maluku Province has interrupted the stability and productivity of the river which serves as one of the sources of life for the ecosystem, including the community living around them. Therefore, the river management and flood mitigation should be professionally handled to be more beneficial and may secure the community and other ecosystem. Flood Management in Selected River Basin (FMSRB) program has contributed to improving the flood mitigation productivity by reducing water volume and water inundation, as the impact of realization of both structural and non-structural activity options, along with the collaborative approach among stakeholder. The result of formative evaluation study with Sub-Directorate of Agriculture and Food team indicates that the impact of structural/infrastructure activities realization to the productivity of flood mitigation is very high at 58.60% and high at 31.40%. While the empowerment-based stakeholder collaboration approach has been affecting to the flood mitigation management performance and good behavior awareness which is very high at 48.60% and high at 35.70%. This study has not been responding 100% since there is still other factor that needs further study.